THE ROLE OF ORGANIZATIONAL CULTURE IN MODERATING THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Umban Adi Jaya; Yayan Sugiarto; Mochamad Fauzi Pebriana Gumilar (Lembaga Penelitian Universitas Pasundan, 2022)
This study aims to determine the role of organizational culture as a moderator on the effect of work discipline on performance. This study uses an associative quantitative approach using a questionnaire distributed to 30 samples with a total sampling technique that has criteria as employees of PT. Jasa Raharja Perwakilan Sukabumi. The instrument testing in this study used validity and reliability tests, data analysis techniques used descriptive analysis, used the classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test and multiple linear regression analysis consisting of hypothesis testing (t test) and analysis of the coefficient of determination (R2). The results of this study indicate that: (1) Work Discipline has a positive effect on Employee Performance (2) Work Discipline, Organizational Culture, and Interaction of Work Discipline with Organizational Culture have a positive effect on Employee Performance (4) The relationship between Work Discipline variables on Employee Performance has an effect of 63.1% and the remaining 36.9% is explained by other variables outside this research model. (5) Then the magnitude of the influence of Work Discipline on Performance after the interaction of Work Discipline with Organizational Culture increases to 71.6% it can be concluded that Organizational Culture strengthens the influence of Work Discipline on Employee Performance of PT. Jasa Raharja Perwakilan Sukabumi